2019
DOI: 10.7577/formakademisk.2489
|View full text |Cite
|
Sign up to set email alerts
|

Developing creative product designs inspired by ethnic cultural heritage

Abstract: Due to colonisation and globalisation, ethnic cultures are changing and Botswana’s ethnic cultures are no exception to this change. This study aims to explore how the ethnic culture of different tribes in Botswana can be used to inspire the design of new products. A case study was conducted with students at the University of Botswana on particular themes of ethnic cultural knowledge, which inspired them to design futuristic innovative products. Visual analysis was used to assess the student designs for how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…By utilising social media, museums, and cultural festivals, the study demonstrated effective strategies to attract appreciation from locals and tourists, which is essential for the long-term sustainability of heritage products. This community-centred approach echoes the findings of Setlhatlhanyo et al [48], which highlights how design students in Botswana can incorporate ethnocultural heritage into innovative product design. Their work demonstrates the potential of education to produce a new generation of designers who not only understand their cultural heritage but also are adept at expressing this ethno-cultural heritage through modern design practices, an approach that can positively contribute to the creative economy.…”
Section: Theme 1: Sustainability and Innovationsupporting
confidence: 67%
See 1 more Smart Citation
“…By utilising social media, museums, and cultural festivals, the study demonstrated effective strategies to attract appreciation from locals and tourists, which is essential for the long-term sustainability of heritage products. This community-centred approach echoes the findings of Setlhatlhanyo et al [48], which highlights how design students in Botswana can incorporate ethnocultural heritage into innovative product design. Their work demonstrates the potential of education to produce a new generation of designers who not only understand their cultural heritage but also are adept at expressing this ethno-cultural heritage through modern design practices, an approach that can positively contribute to the creative economy.…”
Section: Theme 1: Sustainability and Innovationsupporting
confidence: 67%
“…Their investigation of the perspectives of local artisans and traders revealed a common desire to create souvenirs that authentically reflect local culture and heritage, despite the challenges posed by market forces and resource constraints. Setlhatlhanyo et al [48] present a case study from Botswana that demonstrates how ethnocultural heritage can be used to inspire innovative product design among university students. This research example illustrates how engagement with cultural traditions can foster creativity and produce products that resonate with both local and global audiences while contributing to the cultural and economic upliftment of communities.…”
Section: Theme 4: Cultural Identity Expressionmentioning
confidence: 99%
“…In addition to these two identified vectors, predominantly dominant in the Russian scientific space, the view that there is a significant diversification in the tourism experience industry, which due to intensified use of creative technologies in the context of influence on the economic development of Russian regions will only increase, is gaining popularity. Experience and emotions in the context of informatization and digitalization of the economic sphere are transferred from the category of personal individual experiences into the category of business marketing product, which is also subject to a special type of market offer [13].…”
Section: Methodsmentioning
confidence: 99%
“…The uniqueness of traditional Chinese ethnic culture can be fully reflected through the strong ethnic characteristics of traditional ethnic cultural elements. The literature [11] examines how the ethnic cultures of different tribes in Botswana can be used to inspire the design of new products. Through a case study of students at the University of Botswana on a specific theme of ethnic and cultural knowledge to inspire the design of future innovative products, visual analysis was used to assess the inclusion of ethnocultural meanings in the students' clothing designs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In equation (11), N and n are the total number of elements and serial number of the clothing design area, zn R is the radius of the n th clothing design area, and i n d is the distance between the i th ethnic culture element and the center of the design area.…”
Section: ( )mentioning
confidence: 99%